Isolation of Two New Mallotoates with Antifungal and Radical Scavenging Activities from Mallotus phillipensis muell - Afzal, Masood; Zhang, Liqun; J. Cox, Russell; Muhammad, Nawshad; Khan, Shafiullah (Asian Journal of Chemistry, 2015)
Two new chalcone derivatives mallotoate A and mallotoate B were isolated from ethyl acetate fraction of Mallotus philippensis muell. Structure elucidation and the assignment of the isolates were achieved with the help of extensive 1D and 2D NMR studies. These compounds were identified using chemical and spectral data, as mallotoate A and mallotoate B, respectively. Both the compounds (mallotoate A and mallotoate B) showed significant fungicidal activity against Cladosporium cladosporioides in TLC bio-autography method. Using the same method, both mallotoate A and mallotoate B were tested for their antioxidant activities in DPPH radical scavenging activity in which, mallotoate B showed maximum and competitive activity (91.43 ± 0.82 %) against control drugs.